Hubungan Status Gizi dan Kekambuhan Tuberkulosis di Balai Besar Kesehatan Paru Masyarakat Surakarta - Febriyanti , Eka; Amelia, Ayu; Meilanda , Rastria; Syahputra , Ghalib Syukrillah (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Malnutrition can weaken the immune system, thereby increasing the risk of Mycobacterium tuberculosis infection. The aim of this study was to determine the risk of tuberculosis (TB) recurrence associated with the nutritional status of TB patients. This study was conducted at the Surakarta Center for Lung Health in 2017 using a case-control design. The study included 15 individuals in the control group (patients who had been cured of TB) and 15 individuals in the case group (patients who experienced TB recurrence). Inclusion criteria for this study were TB patients aged 18-65 years, both male and female, who had completed the full course of TB treatment, and who had complete data on nutritional status measured through Body Mass Index (BMI) and documented dietary intake in medical records. Patients with metabolic disorders or chronic diseases other than TB that could influence nutritional status were excluded. Data were collected from medical records and analyzed using SPSS version 25. The results showed that patients with poor nutritional status (below the normal BMI) had a significantly higher risk of TB recurrence (p = 0.028). Another finding indicated that patients who had a habit of consuming alcohol also had a higher likelihood of TB recurrence (p = 0.001). The conclusion of this study is that poor nutritional status plays a role in the occurrence of recurrent tuberculosis.